Improving the topical ocular pharmacokinetics of lyophilized cyclosporine A-loaded micelles: formulation, in vitro and in vivo studies - Yinglan Yu; Daquan Chen; Yanan Li; Wenqian Yang; Jiasheng Tu; Yan Shen (Taylor & Francis Group, 2018)
Dry eye syndrome (DES) is one of the most common disorders of the eye for which combined treatment includes modification of the ocular environment and pathogenic therapies. Cyclosporine A (CsA), a immunosuppressive agent, has been demonstrated to be effective for the treatment of DES but is limited clinically by its low ocular bioavailability due to poor water solubility. In this paper, methoxy poly (ethylene glycol)-poly (lactide) polymer (mPEG-PLA) micelles were investigated as alternative vehicles for the solubilization and delivery of CsA to the eye. The in vitro stability indicated that CsA-loaded micellar lyophilized powder was stable for at least 3 months and the release profile showed a sustained release manner of CsA from micelles physically. In vivo ocular distribution studies demonstrated that the micellar formulations exhibited a 4.5-fold increase in retention effect at eyes compared with 0.05% CsA emulsion. In addition, the in vivo pharmacokinetics profile showed that the CsA-loaded micelles could enhance the retention time, achieving longer effect toward the DES. These studies proposed an effective micelle formulation as a novel ocular drug delivery system to improve solubility and bioavailability of ophthalmic CsA-controlled delivery.